RETRACTED: Application of vibration insulating mats in tram track construction - Dudkin E.P.; Garbaruk V.V.; Malakhov M.V.; Sultanov N.N. (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 549, 00001 (2024), https://doi.org/10.1051/e3sconf/202454900001